Innovative Approaches to Superset Asset Templates using Feature‐Based Product Line Engineering. Issue 1 (20th September 2021) - Kobayashi, June; Way, Steve; Krauss, Jonathan P.; Clements, Paul
Abstract: This paper discusses our experience applying Feature‐based Product Line Engineering (PLE) to a product line of hardware modules designed for use in space‐based and airborne systems. Feature‐based PLE involves the automatic configuration of engineering artifacts (maintained as supersets) into product‐specific instances based on that product's feature selections. We observed a 40% reduction in non‐recurring engineering costs in this product line. The paper also discusses an innovative approach we used to extend the ability of the PLE configurator tool to interface with analysis and simulation tools for which no actual tool integration currently exists.